Attachment and social behaviors in the period of transition from preschool to first grade - Seven, S. (My University, 2010)
This study was an investigation of whether or not children's attachment representation and social behaviors were linked to adaptation transition from preschool to elementary school. Eighty students participated in this study. Attachment representation, school adaptation, and social behaviors were measured by Incomplete Stories with Doll Family (Cassidy, 1988), Teacher Assessment of Social Behavior (Cassidy & Asher, 1992), and an Adaptation to School in the First Month Questionnaire developed for this study by the author. One way ANOVA, correlation analysis, and regression analysis were employed to analyze data. Findings showed that there were adaptive problems at elementary school because of insecure attachment and some social behaviors. Attachment and shy-withdrawn behavior were significant predictors of school adaptation with several links among school adaptation, attachment representation, and children's social behaviors. © Society for Personality Research (Inc.).
Keywords: Attachment representation; School adaptation; School transition; Social behaviors